Deep learning of breast papillary lesions. Issue 8 (9th February 2021) - Vielh, Philippe
Abstract : A comprehensive cytologic study of a large series of papillary lesions of the breast suggests a combination of new features to distinguish benign neoplasms from malignant ones.